(untitled) (International Journal of Engineering and Computer Science, 2014)
In the recent years with the development of internet technologies, video technologies have been broadly used in TV, communication and multimedia, So security is required on video data. A technique for embedding data in scrambled AVI video is described. The embedding technique is applied to the video sequence jointly with the video scrambling algorithm. The scrambling operation together with the data embedding process are performed prior to AVI encoding, and the scrambled and data-embedded video is AVI encoded with a minimal increase in the AVI bit rate. In this study a data embedding in scrambled video for the security and authentication of data.